(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Knowledge Management is a process which changes the knowledge of individuals in an organization into the organizational knowledge. This paper states that through assimilating and utilizing the knowledge the organization can achieve success. The importance and relevance is also mentioned in the paper. Knowledge is widely identified as an important organizational resource that boasts the competitive advantage. The significance of Librarians & Information professionals in managing the KM of organizations is described. The challenges and difficulties in KM is mentioned. The role of information technology (IT) in knowledge management (KM), is an indispensible for any organization wishing to use latest and upcoming technologies to manage their knowledge assets. The study shows that knowledge management practice has positive impact on organizational performance.